Reptar to the Rescue! - Stephanie St.Pierre (New York, United States Simon & Schuster, 1997)
There's a really weird toy in the playpen. Chuckie thinks it looks scary. Tommy thinks it looks like fun. But now it's gone berserk it has Angelica's doll in its clutches! Can anyone save the day?
Keywords: Read Aloud -- Read Aloud